Global wine tourism : research, management and marketing - Carlsen, Jack; Charters, Stephen (CABI Pub., 2007)
This book reviews a broad range of topics concerning wine tourism, including regional development, marketing, cellar door experiences, festivals and events, and tours and trails, with insights from case studies in Europe, North America, South Africa, Australia and New Zealand. The book has 20 chapters and a subject index, and will be of interest to wine tourism researchers and stakeholders in the wine and tourism sectors.